Application of Problem Based Learning Assisted by Reward and Punishment to Improve Self-Regulation of Junior High School Students - Gusti Ayu Muthia*; Evita Anggereini (Universitas Syiah Kuala, 2023)
The purpose of this research is to solve learning problems in class, especially student learning independence. Based on the results of student observations in the learning activities that have been carried out, it is known that the independence of student learning is still quite good. In fact, independent learning is one of the success of learning. Based on observations in class, it is known that the independence of student learning is still low. This is indicated by indicators that students are less actively involved in learning in class and are still unable to independently learn to present the results of their discussions in front of the class. This problem occurs because the learning process in the classroom directs students more to work on their student worksheets without carrying out discussion activities that involve student activity in learning. Efforts made to increase learning independence are the problem based learning (PBL) and reward and punishment models. The research method used is the classroom action research (CAR) cycle. The object of research is class VII junior high school students. Collecting research data using observation sheets and student reflection questionnaires. Quantitative descriptive data analysis techniques with very good, good, good enough criteria. Based on the results of the study, it was found that there was an increase in the learning independence of students using the PBL and reward and punishment learning models. This increase occurred after the implementation of learning for 2 cycles